Successful visceral revascularization after acute type A aortic dissection: How to predict visceral ischemia. Issue 5 (2017) - Shiraishi, Manabu; Adachi, Kouichi; Nagano, Hiroshi; Yamaguchi, Atsushi; Adachi, Hideo
No abstract available